PERAN SASTRA ETNIS BATAK DALAM MENGEMBANGKAN PENDIDIKAN KARAKTER - Sinaga, Albertus (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
Regional literature  is part of  a culture that  grew up in  the midst  of  society.  One of that’s is folklore. For the supporters, literature rooted and embedded in social life. In any  customs-customs,  they  always  use  literature  as  a  means  of  communication. Literary  arts,  including  literature  such  as  legends  or  ethnic  Batak  turi-turian  haveexpress  behavior  that  must  be  followed  by  humans.  Utilizing  the  Batak  ethnicliterature  basically  has also  participated  developing  character education.  However, since  this  process  is  an  awareness  and  consciousness  of  the  individual,  it  is necessary to  motivate  others.  This is where  the role of  traditional leaders,  teachers, professors,  literary  or  developer  to  always  familiarize  students  with  literature  and literary areas of Indonesia, including the Batak ethnic regional literature.Keywords: literature of Batak, character Education